2010
DOI: 10.1227/01.neu.0000367449.60796.94
|View full text |Cite
|
Sign up to set email alerts
|

Four-Level Anterior Cervical Discectomy and Fusion With Plate Fixation

Abstract: In carefully selected patients, 4-level anterior cervical discectomy and fusion with plating can be associated with high rates of fusion. The technique is safe and effective for managing multilevel cervical spondylotic myelopathy and may obviate the need for circumferential procedures.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
62
1
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 74 publications
(71 citation statements)
references
References 34 publications
2
62
1
1
Order By: Relevance
“…Khaki et al (48) reported 52% incidence of postoperative dysphagia in patients undergoing anterior cervical spine surgery. It has been postulated that soft tissue swelling is the most common cause of postoperative dysphagia (2,16,(68)(69)(70). However, there are studies supporting the theory that soft tissue swelling is not related to the development of postoperative dysphagia (46,48).…”
Section: Dysphagiamentioning
confidence: 99%
“…Khaki et al (48) reported 52% incidence of postoperative dysphagia in patients undergoing anterior cervical spine surgery. It has been postulated that soft tissue swelling is the most common cause of postoperative dysphagia (2,16,(68)(69)(70). However, there are studies supporting the theory that soft tissue swelling is not related to the development of postoperative dysphagia (46,48).…”
Section: Dysphagiamentioning
confidence: 99%
“…Performing this technique in cases with multilevel cervical spinal canal stenosis is still debatable as regards the type of implant applied and the necessity of supplemental fixation. Studies dealing with four-level cervical discectomy and fusion are scanty and the published reports usually include a limited number of patients [1,2,5,12,13].…”
Section: Why Four-level Cervical Fusionmentioning
confidence: 99%
“…Reviewing the literature as regards multilevel anterior cervical fusion supplemented by stabilisation revealed a tendency towards the application of anterior plating rather than posterior instrumentation [1,5,7,12,13,18]. This is of course advantageous in terms of avoiding performing an additional surgery with a new posterior wound.…”
Section: Why Posterior and Not Anterior Instrumentationmentioning
confidence: 99%
See 2 more Smart Citations